The Auricular Impression: An Alternate Technique - Mark F. Mathews, DDS, MS,1 Alan J. Sutton, DDS, MS,2 (Blackwell Synergy, 2000)
Several conditions necessitate surgical or prosthetic ear reconstruction. If an auricular prosthesis is planned, accurate impressions of both the affected and unaffected ears are essential. This article describes a technique that uses a wax-customized, rigid impression tray and irreversible hydrocolloid to minimize distortion during the procedure.